1989
DOI: 10.1021/j100343a032
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectrum and kinetics of reactions of the acetylperoxy radical

Abstract: Subsequent oxidation yields the radical cation which is unstable in this case and is transformed into Rum(P)(CN')2. Such processes, which involve the transfer of an electron from the metal to the porphyrin ring, have been observed before, but no kinetic data were provided. We were able to measure the rate of the above process as k ~5 X 103 s"1 and to conclude that its rate-determining step is the removal of the carbonyl ligand. Radiolysis of the Ru11 porphyrin in dichloromethane saturated with KOH led to forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
105
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 0 publications
21
105
4
Order By: Relevance
“…This hypothesis was verified by the measurement of pyruvic acid, which is also produced through the same reaction (Andreae et al, 1987). Production of acetic acid by the reactions CH3CO 3 + HO 2, CH3CO 3 + HO2, and CH3CO 3 + CH3CO 2 (Moortgat et aL, 1989a;1989b) is possible considering the supply of CH3CO 2 radicals by atmospheric decomposition of isoprene and acetaldehyde (Talbot et al, 1990). In the wet season, this source is thought to be as strong as vegetation emissions.…”
Section: Introductionmentioning
confidence: 79%
“…This hypothesis was verified by the measurement of pyruvic acid, which is also produced through the same reaction (Andreae et al, 1987). Production of acetic acid by the reactions CH3CO 3 + HO 2, CH3CO 3 + HO2, and CH3CO 3 + CH3CO 2 (Moortgat et aL, 1989a;1989b) is possible considering the supply of CH3CO 2 radicals by atmospheric decomposition of isoprene and acetaldehyde (Talbot et al, 1990). In the wet season, this source is thought to be as strong as vegetation emissions.…”
Section: Introductionmentioning
confidence: 79%
“…Tyndall et al reevaluated the available data on end products of this reaction, particularly those of Crawford et al [333], Moortgat et al [932], and Horie and Moortgat [598], and concluded that channel (a) contributes ~80% while channel (b) contributes ~20% at 298 K. They also concluded that k a /k b = 37 × exp(-660/T) with a large uncertainty in this value. They derived the overall rate coefficient for this reaction, which has been measured only by following the radical concentrations via UV absorption.…”
Section: -41mentioning
confidence: 99%
“…They derived the overall rate coefficient for this reaction, which has been measured only by following the radical concentrations via UV absorption. They based their recommendation mostly on the results of Moortgat et al [932] and Tomas et al [1314]. (Table: 02-25, Note: 02-25) Back to Table D38.…”
Section: -41mentioning
confidence: 99%
“…The photolysis rate for ACET is considerably smaller than the rate for other higher aldehydes (Moortgat et al, 1989). With a smaller photolysis rate, ACET will react more slowly, which can result in higher predicted ACET concentrations and lower concentrations of radicals produced via photolysis.…”
Section: Modifications Of the Cbm-iv Surrogate Approximationmentioning
confidence: 99%